Sleep features and central sensitization symptoms in primary headache patients - de Tommaso, Marina (Springer, 2014)
BACKGROUND: Association between sleep disorders and headache is largely known. The aim of the present study was to evaluate sleep quality and quantity in a large cohort of primary headache patients, in order to correlate these scores with symptoms of central sensitization as allodynia, pericranial tenderness and comorbidity with diffuse muscle-skeletal pain. METHODS: One thousand six hundreds and seventy primary headache out patients were submitted to the Medical Outcomes Study (MOS) within a clinical assessment, consisting of evaluation of frequency of headache, pericranial tenderness, allodynia and coexistence of fibromyalgia syndrome (FM). RESULTS: Ten groups of primary headache patients were individuated, including patients with episodic and chronic migraine and tension type headache, mixed forms, cluster headache and other trigeminal autonomic cephalalgias. Duration but not sleep disturbances score was correlated with symptoms of central sensitization as allodynia and pericranial tenderness in primary headache patients. The association among allodynia, pericranial tenderness and short sleep characterized chronic migraine more than any other primary headache form. Patients presenting with FM comorbidity suffered from sleep disturbances in addition to reduction of sleep duration. CONCLUSION: Self reported duration of sleep seems a useful index to be correlated with allodynia, pericranial tenderness and chronic headache as a therapeutic target to be assessed in forthcoming studies aiming to prevent central sensitization symptoms development.